Implementasi Kuliah Kerja Nyata (KKN) dalam Penguatan Identitas Wilayah dan Mobilitas Masyarakat Desa Taman Negeri - Susi Yulianti; Sofiyatun Maimunah; Nyka Gilang Prayoga; Sri Octa Wulandari; Sopia Icha Maharani; Rana Syadekha; Umar Nurrudin; Siti Julaikah; Siti Fatonah; Wahyu Rama Wirayuda; Khoirurrijal Khoirurrijal (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Community Service Program (KKN) is a form of student service to the community that embodies the tangible contribution of higher education institutions to regional development. This activity is not only oriented towards the application of theories learned in the classroom, but also towards direct experience in the midst of a community rich in social, economic, and cultural dynamics. Through KKN, students learn to understand real issues while striving to provide useful and sustainable solutions. This study focuses on the implementation of KKN in Taman Negeri Village, Way Bungur District, East Lampung Regency. The main program carried out was the creation of hamlet signboards as a step to strengthen regional identity and increase community mobility. The implementation method used a participatory approach, whereby KKN students involved village officials, community leaders, and local residents in the planning, implementation, and evaluation stages. This collaboration made the activities more relevant to the real needs of the community while fostering a sense of ownership of the results achieved. The results of the study show that the installation of hamlet signboards not only facilitates access and movement between areas but also strengthens the identity of the village through a clearer and more structured layout. The signboards give the village a positive image, presenting it as a well-organized and easily accessible area. Thus, KKN has proven to play a strategic role as a means of community empowerment, strengthening cultural identity, fostering cooperation between students and residents, and supporting the realization of sustainable and inclusive village development.